Immune responses and recovery from spotty liver disease in layer birds - Sarah Eastwood; Timothy B. Wilson; Jiongrui Huang; Bronwyn E. Campbell; Peter C. Scott; Robert J. Moore; Thi Thu Hao Van (Poultry Science)
Spotty Liver Disease (SLD), caused by Campylobacter hepaticus, greatly impacts the health and egg production of affected layer hens and is a disease of concern in the poultry industry. This study aimed to enhance the understanding of the immune response in chickens to C. hepaticus infection and their ability to resist reinfections. One hundred- and twenty-layer chickens were allocated to 10 groups and challenged, from one to three times, with C. hepaticus HV10T, with six weeks between each challenge. Blood and cloacal swabs were collected every three weeks to assess antibody responses and Campylobacter presence. Upon necropsy, bile, spleen, jejunum, and blood samples were collected for C. hepaticus detection and host gene expression analysis using qPCR and RNA sequencing. We found that most birds challenged with C. hepaticus for the second or third time did not develop liver lesions even with the presence of C. hepaticus in their bile, suggesting that birds were resistant to disease development following repeated exposure. Anti-C. hepaticus antibodies increased significantly six weeks after a single challenge but reduced from nine weeks. Quantitative PCR demonstrated that C. hepaticus could be recovered from the bile six weeks after a single challenge and increased significantly after a secondary challenge. RNA-seq and qPCR data demonstrate an elevation in pro-inflammatory cytokines, such as interleukin 6 (IL-6) and interleukin 1ß (IL-1ß), after a secondary challenge and down-regulation during a third challenge. Expression of many genes encoding barrier-supporting proteins genes were differentially expressed, with increased expression following a third challenge compared to expression after a single challenge. Comparison of gene expression in tissues of triple to a single challenged birds demonstrated that many genes involved in cytokine activity and the JAK-STAT cascade were down-regulated whereas other immune system pathways were up-regulated. Altogether, the results indicate that over time, immune memory, enhanced barrier function, and a balanced immune response developed, resulting in reduced impact of infection on the birds. These findings show that the impact of C. hepaticus infection can be ameliorated by immune responses and hence indicate that vaccines that induce appropriate protective immune responses should provide an effective tool to reduce SLD in poultry.